The role of homework in the teaching process - Kolak, Ante; Violić, Lenka (2013)
This paper is concerned with the educational element of homework. The subject is
handled both from theoretical and empirical approach. The theoretical part of this paper is
focused on the aim and purpose of homework, as well as the inevitable phenomenon of
homework overexerting the pupils. The issue of advantages and disadvantages of homework
is discussed in great detail, which leads to the concept of schools without homework. The
subject of the quality of homework, its role in the development of creativity and working
habits, the individual approach to designing homework, as well as the use of different social
methods of learning while composing homework is also handled in this paper. Finally, this
paper emphasizes the importance of homework as the ground for cultivating the collaborative
relations between the family home and school.
The empirical part of this paper inquires the attitude of pupils and teachers of an
elementary school, relating to the separate segments of homework (purpose, efficacy,
feedback, affective reactions of pupils and collaboration with parents). The inquiry is focused
on the positions of pupils related to the subject of this study, as well as on determining the
level of the exertion on pupils. The empirical part of this paper is intentionally focused on the
first language classes.
Keywords: nastavni proces; domaća zadaća